Physicochemical dataset from Lima and Douro estuaries (Northwest Portugal)Zenodo - Vânia Freitas; C. Marisa R. Almeida; Sabrina M. Rodrigues; Rúben Pereira; Ana M. Gorito; Jacinto Cunha; Diogo M. Silva; Alexandre van Heerden; Sandra Ramos (Data in Brief)
This article presents a comprehensive dataset of physicochemical data from two urban estuaries on the northern Portuguese coast, based on five sampling campaigns conducted between October 2021 and November 2022. The dataset includes: a) in-situ vertical profiles of water physicochemical parameters (temperature, salinity, pH, turbidity, dissolved oxygen concentration and saturation) collected at 8 sampling stations along the Lima estuary (during both ebb and flood tides) and at 11 stations along the Douro estuary (during flood tides); and b) chemical analyses data, including nutrients (nitrate, nitrite, phosphate, ammonium, and silica), chlorophyll a, total particulate matter, particulate organic matter, and key metal (copper, zinc, cadmium, iron, nickel, lead, manganese, and chromium) concentrations. For the Lima estuary, additional data on dissolved metals concentrations are provided, offering a detailed picture of metal contamination. This dataset provides valuable insights into the estuarine dynamics of two important temperate systems, with a particular focus on anthropogenic influences such as nutrient enrichment and metal contamination. The data have strong reuse potential in environmental monitoring, providing a baseline for assessing anthropogenic changes and offering quality-assured references for studies linking contaminant distribution with hydrodynamic patterns in estuarine environments. Furthermore, such data are relevant to supporting the implementing of environmental policies, such as the EU Water Framework Directive for transitional waters.